Evaluasi Respon Nyeri Pasca Penggunaan Matras Pintar Pereduksi Dekubitus: Pra-Eksperimen Pada Dewasa Sehat - Ni Putu Wulan Purnama Sari; Lanny Agustine; Hartono Pranjoto (Malahayati Nursing Journal, 2024)
ABSTRACT Decubitus is a pressure sore on the skin resulting from a relatively long bed rest position. This health problem often occurs in immobilized patients, and is often found in protruding parts of the bone. In order to prevent the emergence of decubitus in patients on bed rest, and prevent the worsening of wounds in patients who already have decubitus, an innovation of smart pressure reducing mattress was created. Before testing it on patients, it is necessary to test the mattress on healthy adult individuals. This study aims to analyze the correlation between the use of a smart mattress and the emergence of pain responses in healthy adult individuals with indicators of pain, burning sensation and sense of pressure. This quantitative study used a cross-sectional design. The population was healthy adults of productive age. The sample was 29 female nursing students (n=29). Instruments included a smart pressure reducing mattress, observation sheet of body height and weight plus BMI, and pain response questionnaire. Data analysis used the Spearman Rank correlation test (α0.05). The majority reported good evaluation results after using the smart mattress. They expressed strongly agreed with the following statements: they didn't feel any pain (75.86%), burning sensation (75.86%), and sense of pressure on their skin (79.31%). The burning sensation had a strong and significant correlation with the sense of pressure on the skin (p=0.003; ρ=0.528). Using a smart mattress for 40 minutes does not cause a pain response in healthy adult individuals with indicators of not feeling pain, the skin does not feel burning sensation or pressured. There is a strong and significant correlation between burning sensation and the sense of pressure on the skin after 40 minutes lying on the smart mattress. Keywords: Decubitus, Healthy Adults, Smart Mattress, Pain, Burning Sensation, Sense of Pressure.   ABSTRAK Dekubitus merupakan luka tekan pada kulit akibat posisi tirah baring yang relatif lama. Masalah kesehatan ini sering terjadi pada pasien yang imobilisasi, dan sering ditemukan pada bagian tulang yang menonjol. Demi mencegah timbulnya dekubitus pada pasien tirah baring, dan mencegah perburukan luka pada pasien yang sudah memiliki dekubitus, maka dibuatlah inovasi matras pintar pereduksi dekubitus. Sebelum uji coba pada pasien, maka diperlukan uji coba matras pada individu dewasa sehat. Penelitian ini bertujuan untuk menganalisis hubungan penggunaan matras pintar dengan munculnya respon nyeri pada individu dewasa yang sehat dengan indikator sensasi nyeri pada kulit yang meliputi rasa sakit, rasa panas, dan rasa tertekan. Penelitian kuantitatif ini menggunakan desain cross-sectional. Populasi adalah orang dewasa sehat pada usia produktif. Sampel adalah 29 orang mahasiswa keperawatan perempuan (n=29). Instrumen meliputi matras pintar pereduksi dekubitus, lembar observasi TB, BB, dan IMT, serta kuesioner respon nyeri. Analisis data menggunakan uji korelasi Rank Spearman (α0,05). Mayoritas responden melaporkan hasil evaluasi yang baik pasca menggunakan matras pintar. Mereka mengatakan sangat setuju pada pernyataan: tidak merasa sakit (75,86%), kulit tidak merasa panas (75,86%) dan tidak merasa tertekan (79,31%). Rasa panas memiliki korelasi yang kuat dan signifikan dengan rasa tertekan di kulit (p=0,003; ρ=0,528). Penggunaan matras pintar selama 40 menit tidak menimbulkan respon nyeri pada individu dewasa sehat dengan indikator tidak merasa sakit, kulit tidak merasa panas dan tertekan. Ada hubungan yang kuat dan signifikan  antara rasa panas dan rasa tertekan di kulit setelah berbaring selama 40 menit di atas matras pintar. Kata Kunci: Dekubitus, Dewasa Sehat, Matras Pintar, Nyeri, Rasa Panas, Rasa Tertekan